Meaning of Change Agents within Organizational Change - Carlo Gerwing (Journal of Applied Leadership and Management, 2016)
Does an officially appointed change agent overestimate his change related skills and knowledge in comparison to the assessment of his employees?
Keywords: 650; Change Agent; Organizational Change